Positive electrode active material and preparation method and application thereof

By covering the solid electrolyte layer on the surface of the positive electrode active material matrix to form a core-shell structure, the ion and electron conductivity of the positive electrode active material is improved, the problem of poor carrier transmission in solid-state batteries is solved, and the rate performance and cycle stability of the battery are significantly improved.

CN119725700APending Publication Date: 2025-03-28NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411935216.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In a solid-state battery system, due to the problem of solid contact between the positive electrode material and the solid electrolyte, the carrier lithium ions and electrons are poorly transmitted, which suppresses the effective performance of the solid-state battery.

Method used

By covering the solid electrolyte layer on the surface of the positive electrode active material matrix, a core-shell structure is formed, and the ionic conductivity and electron conductivity of the positive electrode active material are improved, so that both it reaches 10-4S/cm or more, promoting efficient transmission of ions and electrons.

Benefits of technology

It significantly improves the rate performance and cycle stability of solid-state batteries, solving the problem of limited performance of solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725700A_ABST
    Figure CN119725700A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode active material and a preparation method and application thereof, the positive electrode active material comprises a positive electrode active material matrix and a solid electrolyte layer, the solid electrolyte layer coats at least part of the surface of the positive electrode active material matrix, the ionic conductivity Ci of the positive electrode active material is greater than or equal to 10 <-4 > S / cm, and the electronic conductivity Ce of the positive electrode active material is greater than or equal to 10 <-4 > S / cm. According to the positive electrode active material disclosed by the invention, the ionic conductivity and the electron conductivity are improved together, and an efficient ion and electron carrier transmission channel is constructed. When the positive electrode active material is applied to the lithium ion battery, the rate capability and the cycling stability of the battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a positive electrode active material, in particular to a positive electrode active material and a preparation method and application thereof, belonging to the technical field of secondary batteries. Background Art

[0002] In the traditional lithium-ion liquid battery system, due to the good permeability of the electrolyte, the battery pole can achieve excellent ion and electron carrier transport, so it has excellent rate performance and energy density and is widely used. However, due to the use of organic liquid electrolytes, there are safety risks such as flammability, explosion and solvent leakage.

[0003] Compared with traditional lithium-ion batteries using liquid electrolytes, solid-state batteries have higher safety performance and are a better choice for solving power battery safety issues. In a solid-state battery system, due to the solid-solid contact problem between the positive electrode material and the solid electrolyte, the uniformity after mixing is poor, and the solid electrolyte cannot be well dispersed into the positive electrode material, which will inhibit the transmission of carrier lithium ions and electrons to a certain extent, thereby restricting the effective performance of solid-state batteries.

[0004] Therefore, improving the ionic conductivity and electronic conductivity of solid-state battery positive electrode active materials has become a technical problem that needs to be solved urgently at this stage. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a positive electrode active material, whose ionic conductivity and electronic conductivity are both within 10 -4 S / cm or above, constructing an efficient carrier transmission channel for ions and electrons. Applying this positive electrode active material to solid-state batteries can effectively improve the battery's rate performance and cycle stability.

[0006] The present invention also provides a method for preparing the above-mentioned positive electrode active material, which has simple process, high maturity, low production cost and is convenient for large-scale mass production.

[0007] The present invention also provides a positive electrode sheet, comprising the positive electrode active material. The positive electrode sheet has a high carrier transmission rate and good electrochemical stability, and can be widely used in various lithium-ion batteries.

[0008] The present invention also provides a battery, comprising the above-mentioned positive electrode active material or positive electrode sheet, which has excellent rate performance and cycle stability.

[0009] In a first aspect, the present invention provides a positive electrode active material, the positive electrode active material comprising a positive electrode active material matrix and a solid electrolyte layer, the solid electrolyte layer is coated on at least a portion of the surface of the positive electrode active material matrix, and the ionic conductivity of the positive electrode active material is Ci≥10 -4S / cm, electronic conductivity Ce≥10 -4 S / cm.

[0010] For the positive electrode active material as described above, the mass ratio of the positive electrode active material matrix to the solid electrolyte layer is λ, and λ>4.

[0011] The positive electrode active material as described above, the chemical formula of the positive electrode active material matrix is ​​Li a Ni x Co y M z A α D β Q γ O2, wherein M is Mn and / or Al, 0.95≤a≤1.05, 0.80≤x<0.98, 0.02≤y≤0.12, 0.0005≤α≤0.01, 0≤β≤0.01, 0.0005≤γ≤0.01, x+y<0.98, z=1-xy;

[0012] The A comprises at least one of fluxing metal elements, grain refining metal elements, and lattice stabilizing metal elements; and / or,

[0013] The D comprises a non-metallic element; and / or,

[0014] The Q includes a metal element or a non-metal element.

[0015] The positive electrode active material as described above, in the positive electrode active material matrix, the lattice stabilizing metal element includes at least one of Al, Zr, and Ti; the fluxing metal element includes at least one of Na, K, Cs, Ca, Sr, Y, Ba, La, and Ce; the grain refining metal element includes at least one of Nb, Ta, W, Mo, and Sb; and / or,

[0016] The D comprises at least one of F, Cl, Br, and I; and / or,

[0017] The Q includes at least one of S, B, P, Al, Zr, Nb, and Ta.

[0018] The positive electrode active material as described above, the 50% cumulative volume particle size D50 of the positive electrode active material matrix C , 3μm≤D50 C ≤9μm; particle size distribution SPAN≤1; and / or,

[0019] The specific surface area of ​​the positive electrode active material matrix is ​​BET, BET≤1.3m 2 / g.

[0020] The positive electrode active material as described above, wherein the bulk porosity ζ of the positive electrode active material matrix is ​​ζ≤5%.

[0021] For the positive electrode active material as described above, the grain boundary length L of the positive electrode active material matrix is ​​1 μm≤L≤5 μm.

[0022] The positive electrode active material as described above, wherein the circularity Re of the positive electrode active material matrix is ​​Re≥0.7; and / or,

[0023] The surface roughness Ra of the positive electrode active material matrix is ​​Ra≤1 μm; and / or,

[0024] The particle strength Rσ of the positive electrode active material matrix is ​​300MPa≤Rσ≤800MPa.

[0025] In the positive electrode active material as described above, the solid electrolyte layer includes at least one of a halide solid electrolyte layer and a sulfide solid electrolyte layer.

[0026] The positive electrode active material as described above, the raw material of the halide solid electrolyte layer includes LiAlCl4, Li3HoCl6, Li3ErCl6, Li3InCl6, Li 2.6 In 0.8 Ta 0.2 Cl6, Li3ScCl6, Li3YCl6, Li3YBr6, Li3YBr2Cl4, Li3YBr3Cl3, Li 2.6 Y 0.5 Zr 0.5 Cl 6.1 、Li2ZrCl6、Li 2.5 In 0.5 Zr 0.5 Cl6、Li 1.75 ZrCl 4.75 O 0.5 、Li3ZrCl4O 1.5 , at least one of LiNbOCl4, LiTaOCl4, LiTaCl6 materials; and / or,

[0027] The sulfide solid electrolyte layer raw materials include Li2S-P2S5, Li3PS4, Li7P3S 11 、Li6PS5Cl、Li 5.5 PS 4.5 Cl 1.5 , Li 7-x PS 6-x Cl x (0<x<1.7), Li 9.54 Si 1.74 P 1.44 S11.7 Cl 0.3 , Li 10 GeP2S 12 At least one of the materials.

[0028] For the positive electrode active material as described above, the thickness of the solid electrolyte layer is 50 nm-3 μm.

[0029] In a second aspect, the present invention provides a method for preparing the positive electrode active material as described above, comprising the following steps:

[0030] Weighing a positive electrode active material matrix and a solid electrolyte layer raw material according to a mass ratio λ, and then physically mixing them to obtain a precursor; then heat-treating the precursor to obtain the positive electrode active material;

[0031] Wherein, the mass ratio λ>4;

[0032] The 50% cumulative volume particle size D50 of the positive electrode active material matrix C 50% cumulative volume particle size D50 of solid electrolyte raw material S Satisfy: 1≤D50 C / D50 S ≤10;

[0033] The temperature of the heat treatment is 50-300° C., the time of the heat treatment is 1 h-5 h, and the atmosphere of the heat treatment is an inert gas.

[0034] In the method for preparing the positive electrode active material as described above, the 50% cumulative volume particle size D50 of the solid electrolyte raw material S Meet 500nm≤D50 S ≤5μm.

[0035] In a third aspect, the present invention provides a positive electrode sheet, comprising the positive electrode active material according to any one of claims 1-11.

[0036] The positive electrode sheet as described above is prepared by a dry process, and the binder is selected from at least one of PVDF, PTFE, polyphenylene sulfide and its derivatives, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, and polyurethane; or,

[0037] The preparation of the positive electrode sheet includes the step of dissolving a binder in a solvent, and the binder includes at least one of acrylic rubber, nitrile rubber, EPDM rubber, styrene-butadiene rubber, fluororubber and silicone rubber; the solvent includes at least one of butyl butyrate, isobutyl isobutyrate, anisole, xylene, heptane, n-butyl ether, acetone and methyl isobutyl ketone.

[0038] In a fourth aspect, the present invention provides a battery, comprising the positive electrode active material as described above, the positive electrode active material prepared by the preparation method as described above, and the positive electrode sheet as described above.

[0039] The positive electrode active material of the present invention comprises a positive electrode active material matrix and a solid electrolyte layer, wherein the solid electrolyte layer is coated on at least a portion of the surface of the positive electrode active material matrix, thereby achieving a common improvement in the ionic conductivity and the electronic conductivity of the positive electrode active material, both of which can reach 10 -4 S / cm or more, and an efficient carrier transport channel for ions and electrons is constructed. Based on this, the rate performance and cycle stability of the battery using this positive electrode active material can be significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the following briefly introduces the drawings required for use in the embodiments of the present invention or related technologies. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0041] Figure 1 (a) is a SEM image of the cathode active material matrix before being coated with electrolyte in Example 1 of the present invention;

[0042] Figure 1 (b) is a SEM image of the cathode active material matrix coated with electrolyte in Example 1 of the present invention;

[0043] Figure 2 Graphs showing the ionic conductivity and electronic conductivity of the positive electrode active material in Example 1 of the present invention;

[0044] Figure 3 Graphs showing the ionic conductivity and electronic conductivity of the positive electrode active material in Example 3 of the present invention. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] The first aspect of the present invention provides a positive electrode active material, comprising a positive electrode active material matrix and a solid electrolyte layer, wherein the solid electrolyte layer is coated on at least a portion of the surface of the positive electrode active material matrix, and the ionic conductivity of the positive electrode active material is Ci≥10-4 S / cm, electronic conductivity Ce≥10 -4 S / cm.

[0047] In the present invention, the positive electrode active material matrix is ​​a compound that can reversibly embed and extract lithium ions, and realizes energy storage and release during the battery charging and discharging process; the raw material of the solid electrolyte layer is a solid material with good ionic conductivity at room temperature, and lithium ions can migrate and transmit inside the battery through its unique diffusion channels. The solid electrolyte layer is coated on at least part of the surface of the positive electrode active material matrix to form a core-shell structure, and the ionic conductivity of the obtained positive electrode active material Ci≥10 -4 S / cm, electronic conductivity Ce≥10 -4 S / cm.

[0048] The positive electrode active material of the present invention is applied to the battery, which is beneficial to improving the performance of the battery in terms of rate performance and cycle stability. The inventor speculates that the reason may be that if only the ionic conductivity of the positive electrode active material is optimized, due to the presence of a space charge layer between the positive electrode active material and the solid electrolyte, there is a high interface impedance between the two, and too low electronic conductivity will hinder the efficient electrochemical reaction. The present invention takes into account the joint improvement of the ionic conductivity and electronic conductivity of the positive electrode active material at the same time, promotes the efficient transmission of ions and electrons inside the battery, improves the charge and discharge efficiency of the battery, and thus significantly improves the rate performance and cycle stability of the battery.

[0049] In order to further improve the electronic conductivity of the positive electrode active material, it is very important to maintain a high mass ratio of the positive electrode active material matrix. In one embodiment, the mass ratio λ of the positive electrode active material matrix to the solid electrolyte layer raw material of the present invention is controlled at λ>4.

[0050] The cathode active material matrix of the present invention can be a cathode active material commonly used in lithium-ion batteries, such as at least one composite oxide of lithium and metals of cobalt, manganese, nickel and combinations thereof. Specifically, it can be at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material, lithium iron phosphate, lithium nickel manganese oxide, lithium-rich manganese-based material, etc.

[0051] Among them, ternary positive electrode materials are widely used as positive electrode active material matrices due to their higher energy density, relative safety and low cost.

[0052] In a specific embodiment, the chemical formula of the positive electrode active material matrix is ​​Li a Ni x Co y M z A α Dβ Q γ O2, wherein M is Mn and / or Al, 0.95≤a≤1.05, 0.80≤x<0.98, 0.02≤y≤0.12, 0.0005≤α≤0.01, 0≤β≤0.01, 0.0005≤γ≤0.01, x+y<0.98, z=1-xy;

[0053] The doping element A includes at least one of a fluxing metal element, a grain refining metal element, and a lattice stabilizing metal element; and / or,

[0054] The doping element D comprises a non-metallic element; and / or,

[0055] The coating element Q includes a metal element or a non-metal element.

[0056] Flux-enhancing metal elements can promote grain growth, lattice-stabilizing metal elements can maintain the structure of the grains and prevent them from collapsing, and grain-refining metal elements can induce orderly arrangement of the lattice.

[0057] The purpose of doping elements is to induce and regulate the size of the primary particles of the positive electrode active material. The fluxing elements can make them grow and improve the electronic conductivity, or the grain-refining elements can flatten the primary particles and improve the ionic conductivity.

[0058] The purpose of coating elements is to form a fast ion conductor layer in situ on the surface of the positive electrode active material matrix, improve the stability of the interface between the positive electrode active material matrix and the electrolyte, reduce the occurrence of side reactions, and improve the long cycle performance of the battery.

[0059] By doping and coating the above elements, the crystal structure and size morphology of the positive electrode active material matrix are designed, and the surface of the positive electrode material matrix is ​​modified in situ to improve the carrier transport characteristics and electrolyte interface stability of the positive electrode active material matrix during the charge and discharge process, thereby improving the cycle stability.

[0060] Further, the lattice stabilizing metal element includes at least one of Al, Zr, and Ti; the fluxing metal element includes at least one of Na, K, Cs, Ca, Sr, Y, Ba, La, and Ce; the grain refining metal element includes at least one of Nb, Ta, W, Mo, and Sb; and / or,

[0061] The doping element D includes at least one of F, Cl, Br, I, and / or

[0062] The coating element Q includes at least one of S, B, P, Al, Zr, Nb, and Ta.

[0063] The present invention does not limit the preparation method of the positive electrode active material matrix. For example, the above-mentioned positive electrode active material matrix can be prepared by the following method: a Ni-Co-M precursor, a lithium source, an A source and a D source are mixed, sintered once to obtain a positive electrode active material intermediate, and then mixed with a Q source, and sintered twice to obtain a positive electrode active material matrix.

[0064] In the preparation method, the Ni-Co-M precursor includes [Ni 1-x-y Co x M y ](OH)2,[Ni 1-x-y Co x M y ]CO3 or [Ni 1-x-y Co x M y ]O x At least one of;

[0065] The A source includes at least one of a halide of a fluxing metal element, an oxide of a fluxing metal element, an oxide of a grain-refining metal element, and a compound of a lattice-stabilizing metal element.

[0066] Sources of D include halides.

[0067] In a specific embodiment, the Ni-Co-M precursor, the lithium source, the A source and the D source are mixed, the primary sintering atmosphere is oxygen, the primary sintering temperature is 800-1000°C, and the primary sintering time is 8-20h. The positive electrode active material intermediate is mixed with the Q source, the secondary sintering atmosphere is oxygen, the secondary sintering temperature is 250-600°C, and the secondary sintering time is 8-20h.

[0068] Among them, the D50 of the positive electrode active material matrix C , particle size distribution SPAN, bulk porosity ζ, circularity Re, specific surface area BET, particle strength Rσ, and grain boundary length L are affected by the primary sintering temperature and time.

[0069] The surface roughness Ra is affected by the temperature and time of the primary sintering and the type of A source.

[0070] Furthermore, by controlling the particle size of the positive electrode active material matrix, it is possible to provide a matrix that is conducive to the coating of the solid electrolyte layer and to ensure the transmission rate of ions and electrons inside it. In one embodiment, the 50% cumulative volume particle size D50 of the positive electrode active material matrix is C , 3μm≤D50 C ≤9μm, particle size distribution SPAN≤1. SPAN is calculated by the following formula: SPAN=(D90–D10) / D50.

[0071] In another specific embodiment, the specific surface area BET of the positive electrode active material matrix satisfies BET≤1.3m 2 / g to reduce the occurrence of side reactions between the positive electrode active material and the electrolyte.

[0072] The present invention can also control the bulk porosity ζ of the cathode active material matrix to satisfy ζ≤5, so as to ensure good contact between the cathode active material matrix and the solid electrolyte layer raw material in the subsequent mixing, and reduce the occurrence of side reactions. It can be calculated based on the pore size distribution through the N2 adsorption and desorption curve.

[0073] In addition, the grain boundary length can be controlled to further control the primary particle size of the positive electrode active material matrix, which is beneficial to the subsequent mixing with the solid electrolyte layer raw materials, thereby improving the interface compatibility between the positive electrode active material and the solid electrolyte layer and providing the ion and electron transmission rate. Therefore, the grain boundary length L of the positive electrode active material can be controlled to meet 1μm≤L≤5μm.

[0074] In order to improve the dispersibility and processing performance of the particles, the present invention also controls the following parameters: Specifically, in one embodiment, the circularity Re of the positive electrode active material matrix is ​​controlled, Re≥0.7.

[0075] In another embodiment, the roughness Ra of the surface of the cathode active material matrix is ​​controlled to be Ra≤1 μm, so that the contact between the cathode active material and the electrolyte material is good.

[0076] Taking into account that the various components of the battery usually need to withstand greater pressure during the battery assembly process, the strength Rσ of the positive electrode active material matrix particles is controlled to meet 300MPa≤Rσ≤800Mpa to ensure that in the subsequent production process, the positive electrode particles will not be crushed under external pressure and induce side reactions.

[0077] Compared with oxide solid electrolyte layer raw materials and polymer solid electrolyte layer raw materials, sulfide and halide solid electrolyte layer raw materials have higher ionic conductivity. Therefore, the solid electrolyte layer raw materials of the present invention include at least one of halide solid electrolyte layer raw materials and sulfide solid electrolyte layer raw materials with higher ionic conductivity.

[0078] Furthermore, the raw materials of the halide solid electrolyte layer include LiAlCl4, Li3HoCl6, Li3ErCl6, Li3InCl6, Li 2.6 In 0.8 Ta 0.2 Cl6, Li3ScCl6, Li3YCl6, Li3YBr6, Li3YBr2Cl4, Li3YBr3Cl3, Li 2.6 Y 0.5 Zr0.5 Cl 6.1 、Li2ZrCl6、Li 2.5 In 0.5 Zr 0.5 Cl6、Li 1.75 ZrCl 4.75 O 0.5 、Li3ZrCl4O 1.5 , LiNbOCl4, LiTaOCl4, LiTaCl6 materials.

[0079] Sulfide solid electrolyte layer raw materials include Li2S-P2S5, Li3PS4, Li7P3S 11 、Li6PS5Cl、Li 5.5 PS 4.5 Cl 1.5 , Li 7-x PS 6-x Cl x (0<x<1.7), Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 , Li 10 GeP2S 12 At least one of the materials.

[0080] Furthermore, the thickness of the solid electrolyte layer of the present invention is 50 nm to 3 μm.

[0081] The second aspect of the present invention also provides a method for preparing the above-mentioned positive electrode active material, which specifically comprises the following steps:

[0082] The positive electrode active material matrix and the solid electrolyte layer raw material are weighed according to a mass ratio λ, and then physically mixed to obtain a precursor; and then the precursor is heat-treated to obtain the positive electrode active material;

[0083] Among them, the mass ratio λ>4, so as to ensure a high mass proportion of the positive electrode active material matrix in the positive electrode active material, thereby improving the overall electronic conductivity of the positive electrode active material.

[0084] It is also important to note that the 50% cumulative volume particle size D50 of the positive electrode active material matrix of the present invention is C 50% cumulative volume particle size D50 of the solid electrolyte layer raw material S Satisfy: 1≤D50 C / D50 S≤10. Generally, increasing the particle size of the positive electrode active material matrix and reducing the particle size of the solid electrolyte layer raw material is beneficial to the contact between the solid electrolyte layer and the positive electrode active material matrix. However, if the particle size of the positive electrode active material matrix is ​​too large, the rate of lithium ion and electron transmission in the positive electrode active material matrix will be reduced. When the particle size of the solid electrolyte layer raw material is too small, its ion conductivity will be greatly reduced. Therefore, the control of the 50% cumulative volume particle size ratio of the positive electrode active material matrix and the solid electrolyte layer raw material is the key to ensuring good contact between the positive electrode active material matrix and the solid electrolyte layer and building an efficient transmission network for ions and electrons.

[0085] In the above preparation method, the present invention does not strictly limit the mixing method, and ball milling, degassing or banburying can be used to achieve uniform dispersion of the precursor I, and the mixing time is 0.5h-3h. Through sufficient mixing, the solid electrolyte layer is coated on the surface of the positive electrode material as much as possible to increase the effective contact area between the two.

[0086] The temperature of the heat treatment is 50-300° C., the time of the heat treatment is 1 h-5 h, and the atmosphere of the heat treatment is an inert gas, which can make the positive electrode active material and the electrolyte material more closely bonded.

[0087] In a specific embodiment, in order to ensure that the ionic conductivity of the solid electrolyte layer is as large as possible and to promote better contact between the solid electrolyte layer and the surface of the positive electrode active material, the 50% cumulative volume particle size D50 of the solid electrolyte layer raw material is controlled. S Meet 500nm≤D50 S ≤5μm.

[0088] In a third aspect, the present invention further provides a positive electrode sheet comprising the above-mentioned positive electrode active material, specifically comprising a positive electrode current collector and a positive electrode active layer formed of the positive electrode active material and arranged on the surface of the positive electrode current collector.

[0089] The above-mentioned positive electrode sheet can be prepared by a dry preparation process or a wet preparation process, and by selecting and adjusting the binder in the two processes, the side reactions of the sulfide and halide solid electrolyte layers can be effectively avoided while ensuring good electrical properties of the positive electrode sheet.

[0090] The present invention does not strictly limit the selection of the conductive agent in the above-mentioned dry / wet preparation process, and the conductive agent can be selected from at least one of SuperP, Ketjen black, VGCF and its derivatives, acetylene black, and graphene.

[0091] Among them, the VGCF conductive agent not only has high conductivity, excellent electrochemical stability, and high specific surface area, but also has good dispersibility and is not easy to agglomerate. Therefore, in a specific embodiment, it is applied to the dry electrode preparation process, which is beneficial to improve the uniformity of the positive electrode active layer.

[0092] In the positive electrode sheet, if too little conductive agent is added, the electronic conductivity of the electrode sheet will deteriorate, while adding too much will reduce the capacity density of the battery. Therefore, the mass ratio of the conductive agent to the positive electrode active material is controlled to satisfy 0.5%≤τ≤3%.

[0093] In addition, the positive electrode sheet current collector of the present invention selects a metal foil with excellent conductivity, high electrochemical stability at the working voltage and compatibility with the positive electrode active material, and can select one of aluminum foil and stainless steel foil.

[0094] Benefiting from the excellent performance of the positive electrode active material, the positive electrode sheet of the present invention has the advantages of high carrier transfer rate and good electrochemical stability. Using it in lithium-ion batteries is beneficial to improving the charge and discharge efficiency and cycle stability of the battery under different currents.

[0095] In a specific embodiment, the following dry preparation steps are provided: a positive electrode active material, a conductive agent and a binder are mixed to obtain an intermediate product I; and then the intermediate product I is combined with a current collector to obtain a positive electrode sheet.

[0096] In the above preparation method, the binder of the dry preparation process includes at least one of PVDF, PTFE, polyphenylene sulfide and its derivatives, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, and polyurethane.

[0097] In addition, the mass ratio of the binder dosage to the positive electrode active material in the dry preparation process can be controlled within the range of 0.5% to 3%, which can not only make the intermediate product I firmly adhere to the current collector, but also avoid excessive binder content that affects the conductivity of the positive electrode sheet.

[0098] Furthermore, in the above preparation method, the present invention does not strictly limit the mixing method, and at least one of ball milling mixing, degassing mixing or banbury mixing can be selected so as to achieve uniform dispersion of the intermediate product I.

[0099] The method of combining the intermediate product I with the current collector of the present invention includes hot pressing molding or roll pressing molding, so that the intermediate product I can be firmly combined with the current collector.

[0100] In another specific embodiment, the wet preparation process comprises the following preparation steps:

[0101] 1) The positive electrode active material and the conductive agent are first mixed to obtain an intermediate product II;

[0102] 2) dissolving the binder in the solvent to form an intermediate III;

[0103] 3) performing a second mixing of the intermediate II and the intermediate III to obtain the intermediate IV;

[0104] 4) The intermediate product IV is combined with the current collector by wet coating to obtain a positive electrode sheet prepared by the wet preparation process.

[0105] In step 1), the present invention does not strictly limit the first mixing method, and at least one of ball milling mixing, degassing mixing or banbury mixing can be selected so as to achieve uniform dispersion of the intermediate product I.

[0106] In step 2), the solvent of the present invention is a weakly polar organic solvent, for example, with a dielectric constant of less than 5 and a mass fraction of a binder of less than 10%, which can avoid side reactions between the solid electrolyte layer and the solvent, and includes at least one of butyl butyrate, isobutyl isobutyrate, anisole, xylene, heptane, n-butyl ether, acetone and methyl isobutyl ketone.

[0107] The binder needs to be evenly dispersed in the solvent system, including at least one of acrylic rubber, nitrile rubber, EPDM rubber, styrene-butadiene rubber, fluororubber and silicone rubber.

[0108] In addition, the amount ratio of the binder to the positive electrode active material is υ, 0.5%≤υ≤3%. The binder within this amount ratio range can not only make the intermediate product IV firmly attached to the current collector, but also avoid excessive content of the binder, which affects the conductivity of the positive electrode sheet.

[0109] In step 3), the present invention does not strictly limit the second mixing method, and at least one of mechanical stirring mixing, ball milling mixing, degassing mixing, and banburying mixing can be selected so as to achieve uniform dispersion of intermediate II and intermediate III.

[0110] Finally, the present invention also provides a battery comprising the above-mentioned positive electrode active material or positive electrode sheet, which has excellent rate performance and cycle stability.

[0111] It is contemplated that the battery of the present invention comprises a lithium ion solid state battery.

[0112] The present invention does not strictly limit the selection of solid electrolytes, and may include one or more of the currently commonly used lithium-ion solid-state battery electrolytes, such as polymer solid electrolytes, oxide solid electrolytes, sulfide solid electrolytes, and halide solid electrolytes.

[0113] Furthermore, the polymer solid electrolyte mainly includes three parts: polymer matrix, lithium salt and additives. Among them, the polymer matrix provides a supporting skeleton and an ion transfer medium, such as at least one of polyoxyethylene (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA) and polyvinylidene fluoride (PVDF); the lithium salt can provide lithium ions, including at least one of LiPF6, LiClO4, LiBF4, LiBOB, LiTFSI, etc.; the types of additives include organic liquids and inorganic fillers, such as at least one of polyethylene glycol (PEG), polyethylene glycol dimethacrylate (PEGDMA), Al2O3, SiO2, and TiO2.

[0114] Oxide solid electrolytes include Li7La3Zr2O 12 , Li 1.5 Al 0.5 Ge 1.5 (PO4)3, La 2 / 3 Sr 1 / 2 At least one of the TiO3 materials.

[0115] Halide solid electrolytes include LiAlCl4, Li3HoCl6, Li3ErCl6, Li3InCl6, Li 2.6 In 0.8 Ta 0.2 Cl6, Li3ScCl6, Li3YCl6, Li3YBr6, Li3YBr2Cl4, Li3YBr3Cl3, Li 2.6 Y 0.5 Zr 0.5 Cl 6.1 、Li2ZrCl6、Li 2.5 In 0.5 Zr 0.5 Cl6、Li 1.75 ZrCl 4.75 O 0.5 、Li3ZrCl4O 1.5 , LiNbOCl4, LiTaOCl4, LiTaCl6 materials.

[0116] Sulfide solid electrolytes include Li2S-P2S5, Li3PS4, Li7P3S 11 、Li6PS5Cl、Li 5.5 PS 4.5 Cl 1.5 , Li 7- x PS 6-x Cl x (0<x<1.7), Li 9.54 Si 1.74P 1.44 S 11.7 Cl 0.3 , Li 10 GeP2S 12 At least one of the materials.

[0117] Furthermore, using the same solid electrolyte as the solid electrolyte in the above-mentioned positive electrode active material is beneficial to reducing the impedance between the positive electrode active material and the electrolyte and improving the carrier transmission rate.

[0118] When preparing lithium-ion solid-state batteries, the positive electrode sheet, the negative electrode sheet and the solid electrolyte layer are wound or stacked to obtain a bare battery cell, and the bare battery cell is hot-pressed at a temperature of 100°C to 300°C and a pressure of 300-500MPa to tightly combine the layers, and then encapsulated in an aluminum-plastic film or a plastic shell.

[0119] The above-mentioned lithium-ion batteries, because they use positive electrode active materials with high ionic conductivity and electronic conductivity, are conducive to the rapid transmission of carriers inside the battery, and have excellent rate performance and cycle stability.

[0120] Example 1

[0121] The method for preparing the positive electrode active material of this embodiment comprises the following steps:

[0122] 1) LiNi 0.8 Co 0.05 Mn 0.15 Al 0.005 Cl 0.015 Zr 0.005 B 0.005 O2 and Li6PS5Cl were weighed at a mass ratio of λ = 5.5, and then mixed by ball milling to obtain a precursor;

[0123] 2) The obtained precursor was then heat-treated in an Ar atmosphere at a temperature of 75° C. for a treatment time of 2 h to obtain a positive electrode active material.

[0124] Among them, LiNi 0.8 Co 0.05 Mn 0.15 Al 0.005 Cl 0.015 Zr 0.005 B 0.005 50% cumulative volume particle size of O2 D50 C The surface area is 5 μm and the BET surface area is 0.42 m 2 / g, bulk porosity ζ is 2.5%, grain boundary length L is 3μm, circularity Re is 0.8, surface roughness Ra is 0.6μm, particle strength Rσ is 350MPa, and particle size distribution SPAN is 0.95;

[0125] D50 of 50% cumulative volume particle size of Li6PS5Cl S 1μm, that is, its D50 C / D50 S is 5, and the thickness of the solid electrolyte layer is 200 nm.

[0126] The positive electrode active material is prepared into a positive electrode sheet according to the following method:

[0127] 1) Mixing the positive electrode active material, VGCF and PTFE by degassing to obtain an intermediate product;

[0128] 2) The intermediate product is then combined with the aluminum foil by hot pressing to obtain a positive electrode sheet prepared by a dry preparation process.

[0129] The mass ratio of PTFE to the positive electrode active material is 1%; the mass ratio of VGCF to the positive electrode active material is 1%.

[0130] Example 2

[0131] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of the embodiment 1, except that the positive electrode active material matrix is ​​Li 1.02 Ni 0.85 Co 0.05 Mn 0.1 Ce 0.005 F 0.015 Zr 0.005 B 0.005 O2, Li 1.02 Ni 0.85 Co 0.0 5Mn 0.1 Ce 0.005 F 0.015 Zr 0.005 B 0.005 O2 D50 C The surface area is 9 μm and the BET surface area is 0.25 m 2 / g, the bulk porosity ζ is 2%, the grain boundary length L is 3.5μm, the circularity Re is 0.75, the surface roughness Ra is 0.8μm, the particle strength Rσ is 300MPa, and the 50% cumulative volume particle size ratio D50 of the positive electrode active material matrix and the solid electrolyte layer raw material is C / D50 S is 9, and the thickness of the solid electrolyte layer is 260nm.

[0132] Example 3

[0133] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of the embodiment 1, except that the solid electrolyte layer raw material is LiAlCl4, and the D50 of LiAlCl4 is S 5 μm, the 50% cumulative volume particle size ratio of the positive electrode active material matrix to the solid electrolyte, D50 C / D50 S is 1, and the thickness of the solid electrolyte layer is 3 μm.

[0134] Example 4

[0135] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of the embodiment 1, except that LiNi 0.8 Co 0.05 Mn 0.15 Al 0.005 Cl 0.015 Zr 0.005 B 0.005 The mass ratio λ of O2 and Li6PS5Cl is 7, and the thickness of the solid electrolyte layer is 60nm.

[0136] Example 5

[0137] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of the embodiment 1, except that LiNi 0.8 Co 0.05 Mn 0.15 Al 0.005 Cl 0.015 Zr 0.005 B 0.005 The mass ratio λ of O2 and Li6PS5Cl is 10, and the thickness of the solid electrolyte layer is 50 nm.

[0138] Example 6

[0139] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of the embodiment 1, except that LiNi 0.8 Co 0.05 Mn 0.15 Al 0.005 Cl 0.015 Zr 0.005 B 0.005 The ratio of the 50% cumulative volume particle size of O2 and Li6PS5Cl, D50 C / D50 S is 1, and the thickness of the solid electrolyte layer is 3 μm.

[0140] Example 7

[0141] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of the embodiment 1, except that LiNi 0.8 Co 0.05 Mn 0.15 Al 0.005 Cl 0.015 Zr 0.005 B 0.005 The ratio of the 50% cumulative volume particle size of O2 and Li6PS5Cl, D50 C / D50 S is 9, and the thickness of the solid electrolyte layer is 800nm.

[0142] Example 8

[0143] The preparation method of the positive electrode active material of this embodiment is basically the same as that of embodiment 1, except that the positive electrode sheet is prepared by the following wet method:

[0144] 1) The positive electrode active material and VGCF are first mixed to obtain an intermediate product I;

[0145] 2) dissolving acrylate rubber in butyl butyrate to form intermediate II;

[0146] 3) performing a second mixing of the intermediate product I and the intermediate product II to obtain the intermediate product III;

[0147] 4) The intermediate product III is combined with the aluminum foil by wet coating to obtain a positive electrode sheet prepared by the wet preparation process.

[0148] Among them, the first mixing method adopts the ball milling mixing method; the ratio of the conductive agent to the positive electrode active material is 1.5%; the specific amount / ratio of the binder to the solvent is 5%; the second mixing method is banbury mixing, and the ratio of the binder to the positive electrode active material is 2%.

[0149] Example 9

[0150] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of embodiment 1, except that LiNi 0.8 Co 0.05 Mn 0.15 Al 0.005 Cl 0.015 Zr 0.005 B 0.005 The grain boundary length of O2 is 8 μm.

[0151] Example 10

[0152] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of embodiment 1, except that LiNi 0.8 Co0.05 Mn 0.15 Al 0.005 Cl 0.015 Zr 0.005 B 0.005 The bulk porosity ζ of O2 is 7%.

[0153] Embodiment 11

[0154] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of the embodiment 1, except that the positive electrode active material matrix LiNi 0.8 Co 0.05 Mn 0.15 Al 0.005 Cl 0.015 Zr 0.005 B 0.005 The grain boundary length is 5 μm.

[0155] Example 12

[0156] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of the embodiment 1, except that the positive electrode active material matrix LiNi 0.8 Co 0.05 Mn 0.15 Al 0.005 Cl 0.015 Zr 0.005 B 0.005 The grain boundary length is 3 μm.

[0157] Example 13

[0158] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of the embodiment 1, except that the positive electrode active material matrix LiNi 0.8 Co 0.05 Mn 0.15 Al 0.005 Cl 0.015 Zr 0.005 B 0.005 The grain boundary length is 2.5 μm.

[0159] Embodiment 14

[0160] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of the embodiment 3, except that the positive electrode active material matrix Li 1.02 Ni 0.85 Co 0.05 Mn 0.1 Ce 0.005 F 0.015 Zr 0.005 B 0.005 O2 D50 C7μm.

[0161] Comparative Example 1

[0162] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of embodiment 1, except that LiNi 0.8 Co 0.05 Mn 0.15 Al 0.005 Cl 0.015 Zr 0.005 B 0.005 The mass ratio λ of O2 and Li6PS5Cl is 2, and the thickness of the solid electrolyte layer is 2.5 μm.

[0163] Comparative Example 2

[0164] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of the embodiment 1, except that the raw material of the solid electrolyte layer is Li7La3Zr2O 12 , Li7La3Zr2O 12 D50 S is 8μm, the cathode active material matrix and Li7La3Zr2O 12 The 50% cumulative volume particle size ratio, D50 C / D50 S is 0.625.

[0165] Comparative Example 3

[0166] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of the embodiment 1, except that the raw material of the solid electrolyte layer is LiNbOCl4. S 400nm, LiNi 0.8 Co 0.05 Mn 0.15 Al 0.005 Cl 0.015 Zr 0.005 B 0.005 The ratio of 50% cumulative volume particle size of O2 and LiNbOCl4, D50 C / D50 S is 12.5.

[0167] Comparative Example 4

[0168] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of the embodiment 1, except that LiNi 0.8 Co 0.05 Mn 0.15 Al 0.005 Cl 0.015 Zr 0.005B 0.005 The mass ratio of O2 and Li6PS5Cl is 2; LiNi 0.8 Co 0.05 Mn 0.15 Al 0.005 Cl 0.015 Zr 0.005 B 0.005 The ratio of the 50% cumulative volume particle size of O2 and Li6PS5Cl, D50 C / D50 S is 12.5, and the thickness of the solid electrolyte layer is 2.5 μm.

[0169] Comparative Example 5

[0170] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of embodiment 3, except that the positive electrode material Li 1.02 Ni 0.85 Co 0.05 Mn 0.1 Ce 0.005 F 0.015 Zr 0.005 B 0.005 O2 D50 S It is 7μm, λ=6.

[0171] Comparative Example 6

[0172] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of the embodiment 3, except that the positive electrode active material matrix Li 1.02 Ni 0.85 Co 0.05 Mn 0.1 Ce 0.005 F 0.015 Zr 0.005 B 0.005 O2 D50 S It is 7μm and λ=4.5.

[0173] Comparative Example 7

[0174] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of the embodiment 3, except that the positive electrode active material matrix Li 1.02 Ni 0.85 Co 0.05 Mn 0.1 Ce 0.005 F 0.015 Zr 0.005 B 0.005 O2 D50 S It is 7μm and λ=6.5.

[0175] Comparative Example 8

[0176] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of the embodiment 3, except that the positive electrode active material matrix Li 1.02 Ni 0.85 Co 0.05 Mn 0.1 Ce 0.005 F 0.015 Zr 0.005 B 0.005 O2 D50 S It is 7μm and λ=3.8.

[0177] Comparative Example 9

[0178] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of the embodiment 3, except that the positive electrode active material matrix Li 1.02 Ni 0.85 Co 0.05 Mn 0.1 Ce 0.005 F 0.015 Zr 0.005 B 0.005 O2 D50 S It is 7μm and λ=2.5.

[0179] Comparative Example 10

[0180] The preparation method of the positive electrode active material and the positive electrode sheet of this embodiment is basically the same as that of the embodiment 3, except that the positive electrode active material matrix Li 1.02 Ni 0.85 Co 0.05 Mn 0.1 Ce 0.005 F 0.015 Zr 0.005 B 0.005 O2 D50 S It is 7μm and λ=1.2.

[0181] After the positive electrode active materials in all Examples 1-14 and Comparative Examples 1-10 are made into positive electrode sheets, they are stacked with negative electrode sheets and solid electrolytes to obtain bare cells, and the bare cells are hot-pressed at 200° C. and 450 MPa to tightly combine the layers, and then encapsulated in an aluminum-plastic film to obtain a lithium-ion solid-state battery.

[0182] Test example:

[0183] 1. D50 C and D50 S : The particle size of the positive electrode active material matrix and the solid electrolyte raw material powder samples was tested using a laser particle size analyzer (MasterSizer 2000).

[0184] 2. BET: Weigh the total weight of the empty test tube and the stopper, soak the positive electrode active material powder sample to be tested in anhydrous ethanol for 4 hours, then take out the powder sample and put it in an oven at 105°C for half an hour, then put the powder sample into the sample tube, weigh the total weight of the powder sample, the test tube and the stopper to calculate the sample mass; turn on the degassing station, put the test tube containing the powder sample into the degassing station at a temperature of 105°C, purge with nitrogen (pure nitrogen) for 30 minutes, cool for 15 minutes, and test at a temperature of 25°C and a humidity of 60% on the machine; take P / P0 with a point in the range of 0.05 to 0.25 as the x-axis and P / V (P0-P) as the Y-axis, draw a graph based on the BET equation for linear fitting, and obtain the slope and intercept of the straight line to calculate the BET specific surface area of ​​the powder sample.

[0185] 3. Bulk porosity: The bulk porosity of the material is tested using the N2 adsorption-desorption curve. The value of the bulk porosity is determined based on the test.

[0186] 4. Grain boundary length L: The grain boundary length of the sample was calculated using Image J software, with 1 μm as the scale, and then the grain boundary length of the positive electrode active material matrix was measured.

[0187] 5. Re: Use Metis software to scan the positive electrode active material particles in SEM to obtain the projected area S and perimeter L. The circularity Re calculation formula is: R = 4πS / L 2 .

[0188] 6. Ra: Place the positive electrode active material on the vacuum adsorption stage of the atomic force microscope. The scanning adopts the tapping measurement mode. The AFM scanning range is 18μm×18μm, the scanning points are 256×256, and the single line measurement time is 1.56s. After the scanning is completed, the positive electrode material is selected and the roughness value Ra is directly read.

[0189] 7. SPAN: Use a laser particle size analyzer to test the particle size of the positive electrode active material, read the D10, D50, and D90 values, SPAN = (D90-D10) / D50.

[0190] 8. Rσ: The particle strength of the positive electrode active material was tested using Shimadzu DUH-211S ultra-micro dynamic hardness tester.

[0191] 9. EIS test: The positive electrode active materials in the embodiments and comparative examples were subjected to AC impedance analysis according to the stainless steel||NCM-LPS||stainless steel mold battery test, with a frequency range of 10 6 -0.01Hz, voltage 10mV.

[0192] 10. Rate performance: At 25°C, the all-solid-state battery is charged at a constant current rate of 0.1C to a voltage of 4.5V, then charged at a constant voltage at a voltage of 4.5V to a current equal to 0.05C, then allowed to stand for 5 minutes, and then discharged at a constant current rate of 0.1C to a voltage of 2.5V. The capacity at this time is recorded as the discharge capacity at a rate of 0.1C; after standing for 10 minutes, the battery is charged at a constant current rate of 1C to a voltage of 4.5V, then charged at a constant voltage at a voltage of 4.5V to a current equal to 0.05C, then allowed to stand for 5 minutes, and then discharged at a constant current rate of 1C to a voltage of 2.5V. The capacity at this time is recorded as the discharge capacity at a rate of 1C. The ratio of the discharge capacity at a rate of 1C to the discharge capacity at a rate of 0.1C is the 1C rate performance.

[0193] 11. Cycle performance: The all-solid-state battery is charged at a constant current of 0.1C to a voltage of 4.5V at 25°C, then charged at a constant voltage of 4.5V to a current equal to 0.05C, then allowed to stand for 5 minutes, and then discharged at a constant current of 0.1C to a voltage of 2.5V. This cycle test is repeated until the capacity decays to 80%, and the number of cycles is recorded.

[0194] 12. Ionic conductivity and electronic conductivity: 1) Place the positive electrode active material into a solid-state battery mold, use a powder cold press to pressurize to 4T, maintain the pressure for 3 minutes and then slowly release the pressure; 2) Place the solid-state battery mold into a pressurized steel shell, tighten the outer steel shell, and make the battery test pressure approximately equal to 100MPa; 3) Place the battery in a 30℃ constant temperature box for 2 hours; 4) Connect both ends of the battery to an electrochemical workstation and use the AC impedance method for testing, where the frequency is set to 0.01-1000000Hz and the amplitude is 10mV, obtain two semicircle spectra, read the value of the intersection of the right side of the first semicircle and the x-axis as R1, read the value of the intersection of the right side of the second semicircle and the x-axis as R2; 5) Disassemble the mold battery, take out the positive electrode sheet and use a micrometer to measure the thickness of the positive electrode sheet, recorded as d (cm); 6) Parallel total conductivity (S / cm) = d / AR1; Electronic conductivity (S / cm) = d / AR2; Ionic conductivity (S / cm) = Parallel total conductivity - electronic conductivity; Where A is the sample area (cm 2 ).

[0195] Figure 1 (a) is a SEM image of the positive electrode active material matrix before being coated with electrolyte in Example 1 of the present invention.

[0196] Figure 1 (b) is a SEM image of the cathode active material matrix after being coated with electrolyte in Example 1 of the present invention.

[0197] From the comparison before and after coating, it can be seen that the electrolyte of Example 1 is evenly coated on the surface of the positive electrode active material matrix, indicating that the positive electrode active material is in good contact with the electrolyte material, which is conducive to the rapid transmission of ions and electrons.

[0198] Figure 2 Graphs showing the ionic conductivity and electronic conductivity of the positive electrode active material in Example 1 of the present invention.

[0199] Figure 3 Graphs showing the ionic conductivity and electronic conductivity of the positive electrode active material in Example 3 of the present invention.

[0200] from Figure 2 and Figure 3 It can be seen that the positive electrode active material of the present invention has excellent ionic conductivity and electronic conductivity.

[0201] Table 1

[0202]

[0203]

[0204] It can be seen from Table 1 that the positive electrode active material of the present invention is applied to a battery, which is beneficial to improving the performance of the battery in terms of rate performance and cycle stability.

[0205] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A positive electrode active material, characterized in that: The positive electrode active material comprises a positive electrode active material matrix and a solid electrolyte layer, wherein the solid electrolyte layer is coated on at least a portion of the surface of the positive electrode active material matrix, and the ionic conductivity of the positive electrode active material is Ci≥10 -4 S / cm, electronic conductivity Ce≥10 -4 S / cm.

2. The positive electrode active material according to claim 1, characterized in that The mass ratio of the positive electrode active material matrix to the solid electrolyte layer is λ, λ>4.

3. The positive electrode active material according to claim 1 or 2, characterized in that: The chemical formula of the positive electrode active material matrix is ​​Li a Ni x Co y M z A α D β Q γ O2, wherein M is Mn and / or Al, 0.95≤a≤1.05, 0.80≤x<0.98, 0.02≤y≤0.12, 0.0005≤α≤0.01, 0≤β≤0.01, 0.0005≤γ≤0.01, x+y<0.98, z=1-xy; The A comprises at least one of fluxing metal elements, grain refining metal elements, and lattice stabilizing metal elements; and / or, The D comprises a non-metallic element; and / or, The Q includes a metal element or a non-metal element.

4. The positive electrode active material according to claim 3, characterized in that In the positive electrode active material matrix, the lattice stabilizing metal element includes at least one of Al, Zr, and Ti; the fluxing metal element includes at least one of Na, K, Cs, Ca, Sr, Y, Ba, La, and Ce; the grain refining metal element includes at least one of Nb, Ta, W, Mo, and Sb; and / or, The D comprises at least one of F, Cl, Br, and I; and / or, The Q includes at least one of S, B, P, Al, Zr, Nb, and Ta.

5. The positive electrode active material according to any one of claims 1 to 4, characterized in that: The 50% cumulative volume particle size D50 of the positive electrode active material matrix C , 3μm≤D50 C ≤9μm; particle size distribution SPAN≤1; and / or, The specific surface area of ​​the positive electrode active material matrix is ​​BET, BET≤1.3m 2 / g.

6. The positive electrode active material according to any one of claims 1 to 5, characterized in that: The bulk porosity ζ of the positive electrode active material matrix is ​​ζ≤5%.

7. The positive electrode active material according to any one of claims 1 to 6, characterized in that: The grain boundary length L of the positive electrode active material matrix is ​​1 μm≤L≤5 μm.

8. The positive electrode active material according to any one of claims 1 to 7, characterized in that: The circularity Re of the positive electrode active material matrix is ​​Re≥0.7; and / or, The surface roughness Ra of the positive electrode active material matrix is ​​Ra≤1 μm; and / or, The particle strength Rσ of the positive electrode active material matrix is ​​300MPa≤Rσ≤800MPa.

9. The positive electrode active material according to any one of claims 1 to 8, characterized in that: The solid electrolyte layer includes at least one of a halide solid electrolyte layer and a sulfide solid electrolyte layer.

10. The positive electrode active material according to claim 9, characterized in that The raw materials of the halide solid electrolyte layer include LiAlCl4, Li3HoCl6, Li3ErCl6, Li3InCl6, Li 2.6 In 0.8 Ta 0.2 Cl6, Li3ScCl6, Li3YCl6, Li3YBr6, Li3YBr2Cl4, Li3YBr3Cl3, Li 2.6 Y 0.5 Zr 0.5 Cl 6.1 、Li2ZrCl6、Li 2.5 In 0.5 Zr 0.5 Cl6、Li 1.75 ZrCl 4.75 O 0.5 、Li3ZrCl4O 1.5 , LiNbOCl4, LiTaOCl4, LiTaCl6 materials; and / or, The sulfide solid electrolyte layer raw materials include Li2S-P2S5, Li3PS4, Li7P3S 11 、Li6PS5Cl、Li 5.5 PS 4.5 Cl 1.5 , Li 7-x PS 6-x Cl x (0<x<1.7), Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 , Li 10 GeP2S 12 At least one of the materials.

11. The positive electrode active material according to any one of claims 1 to 10, characterized in that: The thickness of the solid electrolyte layer is 50 nm-3 μm.

12. A method for preparing a positive electrode active material according to any one of claims 1 to 11, characterized in that: The following steps are involved: Weighing a positive electrode active material matrix and a solid electrolyte layer raw material according to a mass ratio λ, and then physically mixing them to obtain a precursor; then heat-treating the precursor to obtain the positive electrode active material; Wherein, the mass ratio λ>4; The 50% cumulative volume particle size D50 of the positive electrode active material matrix C 50% cumulative volume particle size D50 of solid electrolyte raw material S Satisfy: 1≤D50 C / D50 S ≤10; The temperature of the heat treatment is 50-300° C., the time of the heat treatment is 1 h-5 h, and the atmosphere of the heat treatment is an inert gas.

13. The method for preparing a positive electrode active material according to claim 12, characterized in that: 50% cumulative volume particle size D50 of the solid electrolyte raw material S Meet 500nm≤D50 S ≤5μm.

14. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the positive electrode active material according to any one of claims 1 to 11.

15. The positive electrode sheet according to claim 14, characterized in that: The positive electrode sheet is prepared by a dry process, and the binder is selected from at least one of PVDF, PTFE, polyphenylene sulfide and its derivatives, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, and polyurethane; or, The preparation of the positive electrode sheet includes the step of dissolving a binder in a solvent, and the binder includes at least one of acrylic rubber, nitrile rubber, EPDM rubber, styrene-butadiene rubber, fluororubber and silicone rubber; the solvent includes at least one of butyl butyrate, isobutyl isobutyrate, anisole, xylene, heptane, n-butyl ether, acetone and methyl isobutyl ketone.

16. A battery, characterized in that: The battery comprises the positive electrode active material according to any one of claims 1 to 11, or the positive electrode active material prepared by the preparation method according to claim 12 or 13, or the positive electrode sheet according to claim 14 or 15.